Are Graduating Pediatric Residents Prepared to Perform Infant Lumbar Punctures?: A Multi-Institutional Descriptive Study. Issue 2 (February 2018) - Auerbach, Marc A.; White, Marjorie Lee; Bhargava, Sweta; Zaveri, Pavan; Seelbach, Elizabeth B.; Burns, Rebekah A.; Mehta, Renuka; McAninch, Brett; Fein, Daniel; Chang, Todd P.; Kessler, David O.
Abstract : Objectives: Few published studies describe graduating pediatric residents' procedural skills or success rates. This information would help guide supervisors' decisions about graduating residents' preparedness, training, and supervision needs. This study aimed to measure success rates for graduating pediatric residents performing infant lumbar puncture (LP) during the final months of their training and to describe their experiences performing and supervising infant LPs during the course of their training. Methods: This survey-based study was conducted at 10 academic medical institutions in 2013. The survey consisted of 4 domains: (1) demographics, (2) exposure to infant LP training as an intern, (3) number of LPs performed and supervised during residency, and (4) specific information on the most recent clinical infant LP. Results: One hundred ninety-eight (82%) of 242 eligible graduating residents responded to the survey. A 54% success rate was noted for graduating residents when they were the first provider performing the infant LPs. Success rates were 24% if they were not the first provider to attempt the LP. Overall, graduating residents were supervised on 29% of their LPs, used anesthesia for 29%, and used the early stylet removal technique for 63%. The graduating residents performed a median of 12 infant LPs and supervised others on a median of 5 infant LPs throughout their residency. The vast majority reported feeling confident and prepared to perform this procedure. Conclusions: At the end of residency, graduating pediatric residents were rarely supervised and had low infant LP success rates despite confidence in their skills. However, graduating residents frequently supervised others performing this procedure. Abstract : Supplemental digital content is available in the text.